The Effect of Financial Deepening on Economic Growth in the East African Community - Wanjala, Kevin; Gogo, Pamella (Finance & Economics Review, 2020)
Purpose: The study’s objective is to determine the effect of financial deepening on the economic growth of the East Africa Community bloc. Specifically, it aims to establish the effect of the rate of broad money, credit to the private sector, and the rate of value of the traded stock on economic growth. Methodology: The study used descriptive research design and employed the fixed effect model in regression analysis. Broad money was used to proxy the rate of money supply, credit to the private sector was used to represent credit financing while the volume of the traded stock was used as a measure for financial market investment. Results: The findings revealed that all three indicators of financial deepening namely, broad money, credit to the private sector, and volume of traded stock had a positive and significant effect on economic growth in East Africa Community. The coefficient for broad money was 0.4410, the coefficient for credit to the private sector was 0.4022, while the coefficient for the volume of the traded stock was 0.1367. The model had an F statistic of 103.50, confirming its suitability. Implications: The study recommends that the East Africa Community governments should place more emphasis on the efficiency and of money supply, investment, and distribution by commercial banks. The study also recommends that the governments of East Africa Community countries should continue pursuing policies that promote access to credit such as ensuring that interest rates are low. Additionally, the capital market authorities of the East Africa Community countries should conduct sensitization campaigns to promote high participation in the stock market and other capital market products.